Antenatal, intranatal and postnatal practices in Melghat tribal area: a qualitative study - Goswami, Sourav; Gupta, Subodh S.; Raut, Abhishek V.; Garg, Bishan S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Melghat, the hilly and forest dense area in the northeastern Maharashtra is the home of the Gond and Korku tribes. The maternal and child health indicators in Melghat are poor compared to other parts of Maharashtra. Apart from poor socio-economic development, traditions and social norms prevailing in the area also prevent people to seek reproductive health care. The current study tried to capture the perception of women in reproductive health regarding their practices during the antenatal, natal and postnatal period and reasons for not seeking medical advice during pregnancy or childbirth. Methods: This qualitative study was conducted during September to October 2015 in the selected villages under three PHC areas of Melghat region, where we used in-depth, key informant interviews and focus group discussion with the purposively chosen participants, after taking verbal consent from them. All the interviews were audio recorded which were transcribed for doing the analysis. Ethical clearance was taken from institutional ethical committee. Results: We identified different practices during the antenatal, natal and postnatal period in Melghat, which could be classified into common and deviant. Though some of the mothers go to health facilities for delivery but still there are many others who prefer home delivery due to poor health literacy, family customs, poor communication network, perception regarding quality of health care in government health facilities and more reliance on health seeking from unqualified health care providers and faith healers. Conclusions: More emphasis should be given on counselling for increasing the awareness among the mothers and their families regarding institutional delivery, birth preparedness and maternal deaths in Melghat, along with improvement in quality of services at government health facilities and the inter-sectorial coordination.